New physics in B-s(0) -> J/psi phi decays? - El-Bennich, B. [UNESP]; de Melo, J. P. B. C.; Leitner, O.; Loiseau, B.; Dedonder, J-P (Elsevier B.V., 2012)
After a brief review of B-s(0)-(B) over bar (0)(s) oscillations, we discuss the weak decays B-s(0) -> J/psi phi and B-s(0) -> J/psi f(0)(980) and the ratio R-f0/phi of their decay rates in the light of recent measurements by the LHCb, D(sic) and CDF Collaborations. We point out that the experimental values for R-f0/phi, impose tight limits on new physics contributions to both decay channels. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Flavor physics; CP violation; B-s oscillations; Transition form factors; Non-perturbative QCD